1986
DOI: 10.1080/09291018609359893
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and peptidase activities in reindeer antler throughout the growth cycle

Abstract: Alkaline phosphatase activity increased 10,000-fold over basal levels in reindeer antler during the period of massive growth. The activity was highest in the zone of differentiating chondrogenic cells in the growing tip. The activity in the shaft was lower. PPiase activity was also highest in the antler tip, but compared to alkaline phosphatase, was more tightly membrane-bound. Ca2+, Mg2+-ATPase activity was not so markedly elevated in the tip as were the other activities. During the growth cycle, the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…There is still controversy about whether it acts in the proliferation of mesenchymal cells, expressing chondrogenic and osteogenic functions, or only in the deposition of calcium phosphate salts (e.g. Newbrey and Banks 1975;Warner et al 1983;Salo et al 1986). Recent studies have suggested that ALP may have useful applications for conservation measures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is still controversy about whether it acts in the proliferation of mesenchymal cells, expressing chondrogenic and osteogenic functions, or only in the deposition of calcium phosphate salts (e.g. Newbrey and Banks 1975;Warner et al 1983;Salo et al 1986). Recent studies have suggested that ALP may have useful applications for conservation measures (e.g.…”
Section: Introductionmentioning
confidence: 99%